Pengaruh Rasio Keuangan Terhadap Tindak Kecurangan Pelaporan Keuangan - Ika Listyawati (Universitas Muhammadiyah Semarang, 2020)
This study considers the effect of financial ratios on fraud in financial reporting.While the financial ratios issued are financial leverage, liquidity, profitability, andcapital turnover. Research has been conducted using quantitative methods withsecondary data. Secondary data comes from a list of cases in the FinancialReporting. This research uses purposive sampling method. The total sampleobtained was 32 companies. This company classification consists of 32 companiesthat do financial reporting and 32 companies that do not commit financial reportingby collecting which companies produce the same industry and year of observation.This study uses logistic regression statistical tools while the dependent variable isa dummy (non-metric) variable, while the independent variable is a mixture ofmetric and non-metric variables. The results show that financial leverage, liquidityand capital turnover affect financial reporting fraud, while profitability has noeffect.Keywoard : fraud in financial reporting, financial leverage, liquidity,profitability, and capital turnover.